2021
DOI: 10.1162/qss_a_00156
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing sentiments in peer review reports: Evidence from two science funding agencies

Abstract: Using a novel combination of methods and datasets from two national funding agency contexts, this study explores whether review sentiment can be used as a reliable proxy for understanding peer reviewer opinions. We measure reviewer opinions via their review sentiments both on specific review subjects and on proposals’ overall funding worthiness with three different methods: manual content analysis and two dictionary-based sentiment analysis algorithms (TextBlob and VADER). The reliability of review sentiment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Reviewers with more neutral sentiment scored higher on these two metrics. It has been demonstrated that review sentiment is a strong indicator for predicting proposals’ funding decisions (Luo et al , 2021). Our finding extends this conclusion to review quality.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewers with more neutral sentiment scored higher on these two metrics. It has been demonstrated that review sentiment is a strong indicator for predicting proposals’ funding decisions (Luo et al , 2021). Our finding extends this conclusion to review quality.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a dataset of scientific peer reviews from PeerRead , a deep learning network has been used to predict the acceptance or rejection of articles from peer review reports and to generate the final meta‐review, finding ‘good consistency between the recommended decisions and original decisions’, with 74%–86% accuracy at predicting the binary decision accept/reject, which was better than standard machine learning algorithms and prior bespoke peer review judgement algorithms (Pradhan et al, 2021, p. 237). There is also evidence that sentiment analysis of review reports could be helpful to predict the final decision (acceptance or rejection) of conference papers (Chakraborty et al, 2020; Ghosal, Verma, et al, 2019; Wang & Wan, 2018) or review scores of funding programmes (Luo et al, 2021). For example, PeerJudge uses AI‐assisted sentiment detection to estimate the strength of praise and criticism in peer review reports on academic papers that could be useful for editorial management decisions based on analysing a large number or review reports.…”
Section: Making Review Decisions From Peer Review Commentsmentioning
confidence: 99%
“…The results showed that the addition of sentiment information in review comments significantly improves the prediction ability of the system. Luo et al (2021) discussed whether review sentiment could be used as a reliable proxy for understanding peer reviewer opinions based on the combination of methods and data sets from two national funding agency contexts. The review sentiments on both specific review subjects and proposals' overall funding worthiness measured reviewer opinions.…”
Section: Content Mining Of Peer Reviewmentioning
confidence: 99%